Interrelation of Regional Markets of Labor and Educational Services: Problems and Prospects - Kostenkova, Tatiana Aleksandrovna; Pishchulin, Vladimir Nikolaevich; Shepelev, Maksim Ivanovich (International Journal of Economics and Financial Issues, 2016)
The article considers the problem related to the interrelation of regional markets of labor and educational services through the example of the Lipetsk Region as one of the developed industrial and agricultural regions of Russia. The dynamics of the labor market as a macro-economic indicator witnesses about the directions and tendencies of economic growth of the national economy, as a whole, and economy of specific regions, in particular. Specialists estimate the national labor market ambiguously. On the one hand, there is an opinion that the Russian labor market is in the state of panic and expects abrupt re-focusing on the demand for the labor power. On the other hand, experts mark quiet conditions and a sort of depressiveness that is revealed in maintaining the demand for “popular” professions (economist, sales manager, IT technologies specialist, etc.), but at the same time to a considerably less degree. Because of this, the problem related to adapting to the changed macro-economic conditions of the market of educational services becomes urgent. Herewith, it is necessary to take into account that in Russia there are agricultural, industrial regions and regions with other sectoral specialization where the labor market formation differs from the All-Russian tendencies. The example of the Lipetsk region shows the necessity of active co-operation of employers and educational establishments; eliminating of non-compliance of specialists gained by graduates of educational establishments with the current needs of the contemporary labor market; providing employers with the opportunity to directly influence the formation of the set of areas to prepare students studying in higher educational establishments of the region. The implementation of these events must result in the creation of conditions and stimuli for the development of the human capital assets as a principle resource of the expanded reproduction development of the region. Keywords: labor market, market of educational services, personnel training, regional personnel policy. JEL Classifications: J01, J31, J44, R13